Development and innovation of extension system in the USA and Ukraine - Johnson, S.; Kalna-Dubinyuk, T. P. (НУБіП України, 2018)
It reveals the history of development and the role of extension service in the USA and other countries of the world. The innovative directions of the modern extension system in the USA and its possibilities in Ukraine are shown.
Розробка та інновації системи дорадництва в США та Україні
Розкривається історія розвитку та роль дорадництва – екстеншн сервісу в США і інших країнах світу. Показано інноваційні напрями сучасної системи дорадництва в США та її можливості в України.
Keywords: сталий розвиток; аграрний консалтинг; сільський зелений туризм; sustainable development; agricultural consulting; rural green tourism; nachhaltige Entwicklung; ländlicher Ökotourismus